2021
DOI: 10.1080/20476965.2021.1908176
|View full text |Cite
|
Sign up to set email alerts
|

Using a genetic algorithm to solve a non-linear location allocation problem for specialised children’s ambulances in England and Wales

Abstract: Since 1997, special paediatric intensive care retrieval teams (PICRTs) based in 11 locations across England and Wales have been used to transport sick children from district general hospitals to one of 24 paediatric intensive care units. We develop a location allocation optimisation framework to help inform decisions on the optimal number of locations for each PICRT, where those locations should be, which local hospital each location serves and how many teams should station each location. Our framework allows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The results indicated that adding a floating station could significantly improve the performance of existing EMS systems. Kung et al 24 developed an optimization framework to solve the location-allocation problem of pediatric EMS stations in the U.K. The model aimed to locate EMS stations, determine the number of allocated teams to each station, and identify the hospitals each station serves.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results indicated that adding a floating station could significantly improve the performance of existing EMS systems. Kung et al 24 developed an optimization framework to solve the location-allocation problem of pediatric EMS stations in the U.K. The model aimed to locate EMS stations, determine the number of allocated teams to each station, and identify the hospitals each station serves.…”
Section: Literature Reviewmentioning
confidence: 99%
“…We then worked with clinical partners to define scenarios of interest to explore with more sophisticated modelling, relaxing key assumptions about team availability, travel times and demand. Note that the methods described in this chapter have been published in peer-reviewed journals by King et al 68 and Kung et al 69…”
Section: Overview Of Approachmentioning
confidence: 99%
“…winter vs. non-winter). Note that the methods described in the rest of this section have been published in Kung et al 69…”
Section: Extending the Model By Allowing Stochastic Journey Times And...mentioning
confidence: 99%
“…The association found in this work has the potential for improving allocation of additional resource across the country. As part of the DEPICT study on paediatric critical care retrieval [41], an optimisation framework has been developed that can be used to allocate different numbers of teams to different retrieval locations depending on season and time of day to maximise the availability of teams and minimise time from child referral to the team arriving at the bedside [42]. In that work it was shown that the addition of even one or two teams in key locations could significantly reduce times to bedside.…”
Section: Resource Planningmentioning
confidence: 99%